PENGARUH RADIASI SIMAR GAMMA TERHADAPTANAMAN KACANG HIJAU (Vigna radiata L.) PADA KONDISI SALIN - Nitry Dewi Sari Daeli; Lollie Agustina P. Putri2 Lollie Agustina P. Putri2 Lollie Agustina P. Putri2; Isman Nuriadi2 Isman Nuriadi2 (Jurnal Agroekoteknologi, 2013)
The objective of this research were to find out the influence of gamma ray radiation to mungbean that planted in saline condition, in vegetative and generative phase. This research was conducted in plastic house of Agriculture Faculty, University of North Sumatera, Medan with ± 25 meter altitude above sea level, wich was held in March 2012 to June 2012, using Randomized Block Design, with two factors that were radiation dosages (0, 10, 20 and 30 krad) and NaCl concentrations (0, 2, 4 and 6 g/l). Data were analyzed with ANOVA, and if the ANOVA showed significantly different, the analysis were continued with HSD. The results showed that radiation were significantly influence to plant height (4 and 5 weeks after planted) and harvesting age, salinity were significantly influence to leaf width, ratio of root-canopy dry weight, and root volume, while the interaction of radiation and salinity were not significantly influence to whole parameters.   Key word : mungbean, radiation, salinity, production